Effect of Aloe vera Supplemented Feed on Survival and Growth of Common Carp (Cyprinus carpio L.) - Khan, Injeela; Dhawan, Asha; Ansal, Meera (Indian Journal of Animal Nutrition, 2018)
Common carp (Cyprinus carpio L.) fish were fed with feeds supplemented with A. vera gel (AVG) and A. vera extract (AVE) both @ 1 and 2% (10 and 20 g/kg feed) to evaluate the growth promoting efficacy of aloe (Aloe vera) for 120 days. Feed without A. vera served as control. Water quality and nutrient status of water inboth control and A. vera fed groups remained well within the optimum range for carps. The pond productivity with respect to phytoplankton groups had higher (P